Effects of Smartphone Use on Posture and Gait: A Narrative Review - In Gyu Lee; Seong Jun Son (Applied Sciences, 2025)
Advances in information technology and the widespread adoption of smartphones have improved human convenience and quality of life by facilitating extensive information sharing. However, the increasing frequency and duration of smartphone use is linked to a high risk of musculoskeletal disorders, particularly manifesting as changes in posture and gait. These alterations can lead to various physical issues, including spinal deformities, reduced gait stability, and increased muscle fatigue. Furthermore, excessive smartphone use can negatively affect mental health, contributing to depression, anxiety, and cognitive impairment. This narrative review primarily aims to systematically examine the effects of smartphone-related posture and gait alterations on physical function and identify associated problems. This study systematically summarized individual studies published between 2009, when smartphones first became widespread, and 2024 that investigated the effects of smartphone-induced posture and gait alterations. Through identifying issues related to these alterations, we aim to propose preventive strategies to avoid further complications.